The The Effect of Liquidity and Profitability on Firm Values in Telecommunication Subsector Companies - Francis Hutabarat; Jellyra Sihotang (Journal of Applied Business and Technology, 2020)
The background of this research is how to make investors have a good perception of the company that can be determined through the results of the company's valuation. This research aims to examine the partial and simultaneous relationship between liquidity using the current ratio (CR), and profitability using Return on Assets (ROA) to the company's value of companies using Tobins'Q in telecommunications companies related to IDX (Indonesia Stock Exchange), in 2015-2018. The data get it from financial statements on the Indonesia Stock Exchange with 5 companies as samples. The independent variables of this study are liquidity, profitability and the dependent variable in this study is firm value. This study uses several linear regression methods. the results showing a significant effect between current ratio and Return on Total Assets on firm value and the same results show that there is a significant effect between Return on Total Assets and firm value.